The Effect of Green Product Quality, Price Perception, and Emotional Branding on Green Customer Loyalty in Avoskin Skincare Products - Napitupulu, Yohana Pedra; Nuvriasari, Audita (LifeSciFi, 2026)
Changes in consumer lifestyles that increasingly prioritize environmentally friendly skincare products have contributed to the rapid growth of green skincare in the cosmetic industry. Consumers are becoming more aware of health and environmental sustainability, leading them to prefer skincare products made from natural ingredients that are safe for long-term use. This study aims to analyze the influence of green product quality, price perception, and emotional branding on green customer loyalty toward Avoskin skincare products using a quantitative research approach. The sampling technique employed purposive sampling with a total of 100 respondents who had purchased Avoskin skincare products. Primary data were collected through questionnaires and analyzed using multiple linear regression, while partial hypothesis testing was conducted using the t-test. The results indicate that green product quality, price perception, and emotional branding have a positive and significant effect on green customer loyalty toward Avoskin skincare products. These findings suggest that improving environmentally friendly product quality, maintaining appropriate pricing strategies, and strengthening emotional connections with consumers are important factors in enhancing long-term green customer loyalty.